School Management Strategies to Enhance The Accountability - Oklakorn, Chanawat; Charoenkul, Nuntarat; Siribanpitak, Pruet (Scholar: Human Sciences, 2017)
The objectives of this research were 1) to study the framework of management to enhance the accountability 2) to study the current and desirable states of management to enhance the accountability 3) to analyze strengths, weaknesses, opportunities and treats of management to enhance the accountability and 4) to develop school management strategies to enhance the accountability. The study applied a mixed method approach. The sample were 395 schools under the office of the Basic Education Commission. The instruments used in this study were questionnaires and the strategic evaluation form to testify feasibility and appropriateness. The data were analyzed by frequency, percentage, standard deviation, PNI Modified and content analysis. The research results showed that 1) the framework of management to enhance the accountability consist of five school management: Physical and Emotional well-being of students, Students Learning outcome, Equity for Opportunity to learn of students, Improving capacity of teacher and school management and Parents and community empowerment. 2) In general, the current state of management to enhance the accountability performed at the middle level (x= 3.224). While considering each aspect, physical and emotional well-being of students had the highest average (x= 3.352). The desirable state of management to enhance the accountability was performed at a highest level as a whole. While considering each aspect, equity for opportunity to learn of students had the highest average (x= 4.679). 3) The strengths of management to enhance the accountability were students learning outcome and physical and Emotional well-being of students, while the weakness of management to enhance the accountability were improving capacity of teacher and school management and parents and community empowerment. The opportunity for management to enhance the accountability was technology. While the threats for management to enhance the accountability were the government policy, economy and society. 4) The school management strategies to enhance the accountability were (1) Reforming school management for improving the capacity of teacher and school management to enhance the accountability. (2) Increasing the efficiency of school management focused on equity for opportunity to learn of students to enhance the accountability. (3) Developing the quality of school management for parents and community empowerment to enhance the accountability. (4) Promoting school management of students learning outcome to enhance the accountability. (5) Driving school management of physical and emotional well-being of students to enhance the accountability.